Characteristics of medicine use for children with asthma in China: a nationwide population-based study - Wu, Ping; Xu, Baoping; Shen, Adong; Zeng, Huasong; Shen, Kunling (BMC pediatrics, 2022)
To analyze the asthma medication use in Chinese children of different age groups, regions, and levels of cities in China, based on the 2015 Healthcare Insurance Data in China. The China Healthcare Insurance Research Association (CHIRA) database was searched for children from 0 to 14 years old diagnosed as asthma based on the "J45" and "J46" coded in ICD-10. A cross-sectional study design was employed. A total of 308,550 children were identified, all of whom were treated under the coverage of healthcare insurance. Among them, 2,468 children were eligible for inclusion in the present study. Compared with the current status of asthma care in European and American countries, under the guidelines for the diagnosis and treatment of asthma in China, the use percentages of ICS and short-acting β receptor agonist in children with asthma in China were lower, but the use percentages of oral corticosteroids, long-acting β receptor agonist, and theophylline (especially intravenous theophylline) were higher, especially in the Central and West China. The asthma medication use was attributed to many factors, thus efforts are still needed to further popularize the GINA programs and China's guidelines for asthma diagnosis and treatment, especially in the Central and West China.